Advances in transarterial therapies for hepatocellular carcinoma: is novel technology leading to better outcomes?. (April 2016) - de Baere, Thierry; Tselikas, Lambros; Deschamps, Frederic; Boige, Valerie; Ducreux, Michel; Hollebecque, Antoine
Conventional transarterial chemoembolization (c-TACE) was validated in 2002 for intermediate stage hepatocellular carcinoma (HCC). Recent improvements in overall survival after c-TACE in HCC is linked to both better patient selection, and improvement in treatment technologies: catheter, image guidance and new drug delivery platforms. Drug eluting beads (DEBs) demonstrated a benefit over c-TACE in pharmacokinetic studies; however, two randomized studies comparing c-TACE and DEB-TACE demonstrated no benefit of DEB-TACE in response rate or overall survival. Delivery platforms loaded with yttrium-90 deliver selective internal radiation therapy, which opens a new field of therapy for HCC. Future improvement in intra-arterial therapies will include resorbable loadable embolic material, new emulsion used for c-TACE and platforms releasing multikinase inhibitors.